Healing the nation: royalist visionaries, Cromwell, and the restoration of Charles II. Issue 4 (8th August 2019) - Capp, Bernard
ABSTRACT: The radical visionaries of the civil war era had several royalist counterparts, today often overlooked. This article examines the three most significant: John Sanders of Harborne, Walter Gostelo, and Arise Evans. God, they claimed, had directed them to press Cromwell to restore Charles II, perhaps through a marriage alliance. This alone could settle the nation, and it would usher in a millennial age of peace. Sanders combined support for the crown and Church with a remarkable call for the nailers of Birmingham to strike against their oppressive employers. His family responded to his visionary mission with deep hostility. Evans attracted far greater public interest; he and Gostelo were able to present their ideas to Cromwell in person, and Gostelo travelled to the exiled royal court. The visionaries' message, if ultimately unacceptable, spoke to the concerns of many contemporaries anxious and uncertain about the future.